Relationship between Whole Blood Viscosity and Lesion Severity in Coronary Artery Disease - Ceyhun, Gökhan; Birdal, Oğuzhan (International Journal of Angiology, 2021)
Objective This article investigates the relationship of fractional flow reserve (FFR) with whole blood viscosity (WBV) in patients who were diagnosed with chronic coronary syndrome and significant stenosis in the major coronary arteries and underwent the measurement of FFR.Material and Method In the FFR measurements performed to evaluate the severity of coronary artery stenosis, 160 patients were included in the study and divided into two groups as follows: 80 with significant stenosis and 80 with nonsignificant stenosis. WBVs at low shear rate (LSR) and high shear rate (HSR) were compared between the patients in the significant and nonsignificant coronary artery stenosis groups.Results In the group with FFR < 0.80 and significant coronary artery stenosis, WBV was significantly higher compared with the group with nonsignificant coronary artery stenosis in terms of both HSR (19.33 ± 0.84) and LSR (81.19 ± 14.20) (p < 0.001). In the multivariate logistic regression analysis, HSR and LSR were independent predictors of significant coronary artery stenosis (HSR: odds ratio: 1.67, 95% confidence interval: 1.17–2.64; LSR: odds ratio: 2.46, 95% confidence interval: 2.19–2.78). In the receiver operating characteristic (ROC) curve analysis, when the cutoff value of WBV at LSR was taken as 79.23, it had 58.42% sensitivity and 62.13% specificity for the prediction of significant coronary artery stenosis (area under the ROC curve: 0.628, p < 0.001).Conclusion WBV, an inexpensive biomarker that can be easily calculated prior to coronary angiography, was higher in patients with functionally severe coronary artery stenosis, and thus could be a useful marker in predicting the hemodynamic severity of coronary artery stenosis in patients with chronic coronary syndrome.
Keywords: whole blood viscosity; coronary artery disease; fractional flow reserve